The End of Peasantry: Peasants and Cities in Colonial Java in The Early Twentieth Century - Arif Akhyat (Humaniora, 2020)
This paper aims to explain the decline of the peasant community in Semarang City, Central Java, by exploring the historical shifts in the city's spatial structures and livelihoods. Spatial changes and the issue of subsistence ethics simultaneously will be used to explain the peasant community’s exclusion in the city. In the early of modernization Semarang, peasant economy collapsed by deagrarianization process and  creating patterns of domestication, adaptation, and marginalization. This adaptation was necessary to reaffirm longstanding communal bonds that had contributed significantly to the city's historical growth. At the same time, however, the urban peasant community was excluded, as agrarian subsistence ethics required it to remain subordinate, while the city's new economic system limited or failed their social mobility. As a result, the peasant community was increasingly left behind by the city's social transformation. Discussing the end of the peasantry during decolonialization process is as a way to find out the consolidation ability of the peasant community during a depeasantization process.  This paper will answer the question how socio-economic modifications were made by peasant to navigate with gigantic changes in the city during decolonialization Semarang? Using the historical method, an analysis of a peasant community seems to be more appropriate for obtaining the process of ending of the peasantry and it took into account for both the continuity and the discontinuity process. This paper is expected to provide new facts that have implications for the writing of the Javanese urban historiography which has never been present in Indonesian historiography.